Instruksi Gubernur DKI Jakarta Tentang Penyelenggaraan Balap Formula E Dalam Tinjauan Siyasah Islam - Rasyid Tanjung (Al Ahkam, 2021)
This study examines the instructions of the Governor of DKI Jakarta regarding the implementation of formula E racing in DKI Jakarta from the point of view of siyasah dusturiyah (Islamic legislation), Siyasah Maliyah (Islamic economic politics) and siyasah kharijiyyah (foreign relations in Islam). The method used is normative legal research with literature study (documentation study). The results of this study are that the existence of the DKI Jakarta Governor's Instruction Number 49 of 2021 concerning the Settlement of Regional Priority Issues for 2020-2021 is in accordance with the siyāsah dustūriyah and is in line with Government Regulation Number 55 of 2019 concerning the Acceleration of the Battery-Based Electric Vehicle Program (Battery Elecktic Vehicle). For Road Transportation. Judging from the siyasa maliyah, the implementation of Formula E racing provides the benefit of the people, namely giving a positive impact on the economy of Jakarta in particular and Indonesia in general from the economic downturn due to the covid-19 outbreak. In the perspective of siyasah kharijiyah, the cooperative relationship between the DKI Jakarta government and Formula E Operations (FEO) must be in accordance with the principles of contract law or cooperation. In addition, both parties must also respect each other, benefit each other and not violate the cooperative relationship and the cooperation does not conflict with morals. The cooperative relationship is not only active, but also appreciative.